The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.isci.2021.103030
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptome identifies FCGR3B upregulated subtype of alveolar macrophages in patients with critical COVID-19

Abstract: Understanding host cell heterogeneity is critical for unravelling disease mechanism. Utilizing large scale single-cell transcriptomics, we analysed multiple tissue specimens from patients with life-threatening COVID-19 pneumonia, compared with healthy controls. We identified a subtype of monocyte-derived alveolar macrophages (MoAM) where genes associated with severe COVID-19 comorbidities are significantly upregulated in broncho-alveolar lavage fluid (BALF) of critical cases. FCGR3B cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 61 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…Unfortunately, currently, there is no systematic classification of macrophage subtypes in emphysema or COPD. The single-cell sequencing study by Nassir et al in patients with critical COVID-19 is of significance, in which monocyte-derived alveolar macrophages were divided into two clusters and one macrophage subtype, labeled CCL3L1 and FCGR3B, was identified to be significantly upregulated in critical COVID-19 (31). Since the classification and function of macrophage subtypes in emphysema are not yet clear, many studies still refer to the classification of M1 and M2 subtypes (32,33), exerting pro-inflammatory and repairing functions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, currently, there is no systematic classification of macrophage subtypes in emphysema or COPD. The single-cell sequencing study by Nassir et al in patients with critical COVID-19 is of significance, in which monocyte-derived alveolar macrophages were divided into two clusters and one macrophage subtype, labeled CCL3L1 and FCGR3B, was identified to be significantly upregulated in critical COVID-19 (31). Since the classification and function of macrophage subtypes in emphysema are not yet clear, many studies still refer to the classification of M1 and M2 subtypes (32,33), exerting pro-inflammatory and repairing functions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…FCN1 was apt to assist and improve the inflammatory response of organism (31), which explained why asymptomatic patients had the mild or insignificant clinical symptoms. Furthermore, FCNR3B was specifically expressed in critical patients, and the immunoglobulin Fc receptor regulated the adaptive and innate immune responses, which was essential against infection and prevention of chronic inflammation and autoimmune diseases (32). NK and T cells were the immune effector cells against virus infection (33).…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies by Grant et al ( 27 ) identified a slowly unfolding, spatially restricted alveolitis in patients infected with SARS-CoV-2 in which alveolar macrophages containing the virus and T cells form a positive feedback loop that drives a persistent alveolar inflammation. Other work identified an upregulation of specific macrophage ( 28 ) or T cell subsets such as CD16 + T cells that directly promote lung microvascular endothelial cell injury ( 29 ).…”
Section: Conceptual Barriersmentioning
confidence: 99%